IC 9419 A Method To Measure Gas Levels During Auger Mining Of Coal - Jon C. Volkwein (The National Institute for Occupational Safety and Health (NIOSH), 1994)
The U.S. Bureau of Mines has developed a method to measure methane and other gases during the auger mining of coal. An intrinsically safe commercial gas detector with a built-in data logger was mounted in the center of the hollow conveying auger. A sampling head through the wall of the auger conducted a gas sample to the detector. Results showed that gas levels can be monitored on a continuous basis during the auger mining of coal and the data retrieved upon completion of the hole.